2008
DOI: 10.1038/ncb1706
|View full text |Cite
|
Sign up to set email alerts
|

elipsa is an early determinant of ciliogenesis that links the IFT particle to membrane-associated small GTPase Rab8

Abstract: The formation and function of cilia involves the movement of intraflagellar transport (IFT) particles underneath the ciliary membrane, along axonemal microtubules. Although this process has been studied extensively, its molecular basis remains incompletely understood. For example, it is unknown how the IFT particle interacts with transmembrane proteins. To study the IFT particle further, we examined elipsa, a locus characterized by mutations that cause particularly early ciliogenesis defects in zebrafish. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
232
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(245 citation statements)
references
References 34 publications
11
232
0
2
Order By: Relevance
“…Consistent with previously published data (Omori et al , 2008; Follit et al , 2009), we found that purified IFT54 associates with IFT20 via the coiled‐coil domain and not via the CH domain (Appendix Fig S2C and D). Similarly, the coiled‐coil regions of IFT38 and IFT57 were sufficient for IFT57/38 complex formation (Fig 2D, lane 5 and Appendix Fig S2E).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with previously published data (Omori et al , 2008; Follit et al , 2009), we found that purified IFT54 associates with IFT20 via the coiled‐coil domain and not via the CH domain (Appendix Fig S2C and D). Similarly, the coiled‐coil regions of IFT38 and IFT57 were sufficient for IFT57/38 complex formation (Fig 2D, lane 5 and Appendix Fig S2E).…”
Section: Resultssupporting
confidence: 93%
“…The N‐terminal CH domains of IFT57/38 mediate the contacts to IFT80 and IFT172, whereas the C‐terminal coiled‐coils allow for IFT57/38 hetero‐dimer formation and links to the IFT54/20 hetero‐dimer (Fig 2 and Appendix Fig S2). The interaction between IFT54 and IFT20 is in agreement with previously published data (Omori et al , 2008; Follit et al , 2009), whereas the interaction between IFT57 and IFT38 was not previously reported. Additionally, IFT57/38 mediates the contacts between the two IFT‐B subcomplexes by binding directly to IFT88/52N of IFT‐B1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The heatshock promoter has been used, for example, to drive the expression of a crumbs gene from a Tol2-based vector in the zebrafish retinal neuroepithelium. This approach produced expression in nearly half of neuroepithelial cells (Omori et al, 2008).…”
Section: Approaches To Genementioning
confidence: 99%